2017
DOI: 10.1080/00071668.2016.1268252
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles and associations of adiponectin and adiponectin receptors with intramuscular fat in Tibetan chicken

Abstract: 1. Adiponectin and its receptors (ADIPOR1 and ADIPOR2) are novel endocrine systems that act at various levels to modulate glucose and lipid metabolism. This study was designed to investigate the spatial expression of adiponectin, ADIPOR1 and ADIPOR2 genes in various tissues in Tibetan chicken. The temporal expression of adiponectin and its receptor mRNAs were also studied in adipose tissue, breast muscle and thigh muscle and the correlations of the levels of adiponectin, ADIPOR1 and ADIPOR2 mRNA with the conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Similarly, the chicken ADIPOR2 cDNA was 76–78% homologous to human, mouse, or pig ADIPOR2 cDNA, while the deduced protein sequence was 82% similar to mammalian ADIPOR2 [ 122 ]. Adiponectin and adiponectin receptor genes are ubiquitously expressed in various tissues ( Table 1 ) [ 123 , 124 ], and the expression of the adiponectin system (adiponectin, ADIPOR1, and ADIPOR2) in adipose tissue and muscle depends on the gender and age of the animals [ 125 ]. In adipose tissue, adiponectin mRNA was higher in 154-day-old females than in males and ADIPOR1 mRNA was higher in 154-day-old males than in females.…”
Section: Adiponectinmentioning
confidence: 99%
“…Similarly, the chicken ADIPOR2 cDNA was 76–78% homologous to human, mouse, or pig ADIPOR2 cDNA, while the deduced protein sequence was 82% similar to mammalian ADIPOR2 [ 122 ]. Adiponectin and adiponectin receptor genes are ubiquitously expressed in various tissues ( Table 1 ) [ 123 , 124 ], and the expression of the adiponectin system (adiponectin, ADIPOR1, and ADIPOR2) in adipose tissue and muscle depends on the gender and age of the animals [ 125 ]. In adipose tissue, adiponectin mRNA was higher in 154-day-old females than in males and ADIPOR1 mRNA was higher in 154-day-old males than in females.…”
Section: Adiponectinmentioning
confidence: 99%
“…It was also discovered that Adiponectin receptor agonists (AdipoRon) could activate the expression of adiponectin and then limit the occurrence of these metabolic diseases and inflammatory responses via regulating AMPK and PPARα signaling pathways ( Yamauchi et al., 2003 ; Kita et al., 2019 ; Adiyaman et al., 2020 ). In recent years, a number of studies have reported that adiponectin and its receptors are widely present in various tissues and cell types, including the reproductive tissues of human and animals ( Lord et al., 2005 ; Nigro et al., 2013 ; Smolinska et al., 2014 ; Zhang et al., 2017 ), which indicated that it may be involved in multiple physiological processes, especially the reproductive process ( Chabrolle et al., 2007 ; Maillard et al., 2010 ; Kamil et al., 2018 ). For example, it has been proved that AdipoRon fed mice could experience cardiac hypertrophy and fibrosis caused by over-pressure in remission, which implied to affect by the activation of the AMPK signaling pathway ( Ning et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (2017) also found that the highest levels of PPAR-γ are expressed at approximately 150 days in female Wuhua chickens and positively correlated with IMF (r = 0.875, P = 0.065). The mRNA expression levels of ADIPOR1 and ADIPOR2 genes in the thigh muscle of male Tibetan chickens are significantly positively correlated with IMF (Zhang et al 2017). The expression of A-FABP gene is also positively associated with IMF content in chickens (Wang et al 2017).…”
Section: Discussionmentioning
confidence: 92%